Optimalisasi Kualitas Hidup Lansia Melalui Skrining Kesehatan di Bank BPD Bali Cabang Tabanan - Widari, Komang Laksmi (Jurnal Abdi Mahosada, 2026)
The increasing proportion of the elderly in Indonesia is accompanied by a high prevalence of non-communicable diseases such as hypertension and diabetes, necessitating early detection and ongoing education. The elderly are already a high-risk group due to sedentary lifestyles, prior work stress, and post-retirement socioeconomic changes. The purpose of this community service activity is to describe the implementation and results of health check-ups and health education for elderly bank customers. The community service was conducted using a descriptive design, involving blood pressure measurements, random blood glucose tests, cholesterol levels, and health education on healthy lifestyles for elderly customers present at the bank. The majority of participants had normal examination results, but some elderly individuals showed blood pressure and glucose levels above reference values and were referred for further evaluation. Health education enhanced the elderly's understanding of the importance of routine check-ups and adopting healthy lifestyles. Periodic health screenings and structured education in the Bank BPD Bali environment have the potential to improve awareness and quality of life among retired elderly, and this model can be replicated for other formal sector retirees. Keywords: Elderly, Health Education, Blood Pressure Screening, Blood Glucose, Cholesterol, Uric Acidtemplate-abdi-mahosada.doc​